2020
DOI: 10.3390/su12062554
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Mobile Phone Dependence Amongst Young People—Educational Implications

Abstract: The use of mobile devices facilitates access to knowledge and is at the base of the education of the future. Although the digital society has contributed a number of benefits, it has also been associated with worrying behaviors. The study design consisted of a quantitative approach that was descriptive, inferential and ex post facto in nature. Its purpose was to better understand the opinion of young people regarding smartphone use and describe dependence deriving from regular use. The sample was formed of 420… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
1
12
0
3
Order By: Relevance
“…Although in a low percentage (4.6%) we are concerned about the fact that there are students who lack Wifi connection which deprives them from following distance learning, and what is worse of keeping fluid social contact through social networks. However, we think that the widespread use of mobile phones alleviates the difficulty of social interaction as we have already pointed out in previous studies (Martínez-Sánchez et al, 2020).…”
Section: Descriptive Analysis Cc/covid-19mentioning
confidence: 57%
“…Although in a low percentage (4.6%) we are concerned about the fact that there are students who lack Wifi connection which deprives them from following distance learning, and what is worse of keeping fluid social contact through social networks. However, we think that the widespread use of mobile phones alleviates the difficulty of social interaction as we have already pointed out in previous studies (Martínez-Sánchez et al, 2020).…”
Section: Descriptive Analysis Cc/covid-19mentioning
confidence: 57%
“…The explanation for these divergences could lie in the impact of sociocultural factors in problematic smartphone use-an issue that has already been stated by authors such as Mei et al [59], Aguilera-Manrique et al [25], and Panova et al [54]. However, it should be taken into account that, as multiple studies [31,39,55,58] have shown, the problematic use of the smartphone is closely connected to participation in social networks. Therefore, another possible reason for these differences may lie in the greater use of social networks among Spanish university students, a factor the clarification of which will require more cross-cultural analysis.…”
Section: Discussionmentioning
confidence: 94%
“…In the comparison between the usage patterns of the participants from both universities, it is the Spanish students who show signs of more excessive smartphone use, approaching nomophobia. For this reason, it is necessary to design educational actions that favour a more balanced and rational use of this type of technology [58]. This is especially true if we hold out the hope that ICTs will contribute to the attainment of more sustainable development for humankind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was assumed that most students participated in the web-based quiz using their smartphones, considering the widespread use of these devices among youngsters worldwide, including college and university students (Chen et al, 2017). The increase in the number of smartphone users is followed by criticisms about the various downsides in the use of smart devices, including Internet or smartphone addiction (Tateno et al, 2019a;Tateno et al, 2019b;Martínez-Sánchez et al, 2020). However, several studies suggest that the use of such technologies has a positive effect on academic performance (Ma et al, 2018;Han and Yi, 2019).…”
Section: Discussionmentioning
confidence: 99%